Effect of Mixing Wheat Flour with Pumpkin and Dates on the Nutritional and Sensory Characteristics of Cake - Aljahani, Amani Hamzah; Al-Khuarieef, Amal Nassir (Pakistan Journal of Nutrition, 2017)
Background: The development of food products is a major goal of the food industry. Pumpkin is a rich source of nutrients that may help improve products. Objective: The aim of this study was to evaluate the effect of replacing wheat flour with pumpkin or both pumpkin and dates on the chemical and sensory characteristics of cake. Methodology: Three different cakes were prepared: (1) Control, (2) 50% of the wheat flour replaced with pumpkin mash and (3) 50% of the wheat flour replaced with 30% pumpkin and 20% dates. The moisture, protein, fat, ash, fiber, carbohydrate and fatty acid contents were measured. Results: There were no significant differences (p<0.05) among the control, pumpkin and pumpkin and date cakes in terms of protein, fat and ash content (p = 4.62, 4.51 and 4.0, respectively). A sensory evaluation showed that the pumpkin and date cake and control cake were not significantly different (p<0.05) in terms of odor, texture and overall acceptability. The cake supplemented with pumpkin and dates had increased essential fatty acid content. The pumpkin cake had the highest scores for all quality attributes compared to others, likely because of the stronger pumpkin odor and taste. Moreover, the color appeared to be a very important criterion for initial acceptability of the cakes by consumers. The color of the pumpkin cake was significantly affected (p<0.05) by the addition of pumpkin. Conclusion: Pumpkins can be a good source for the development of food products because of their ability to improve the appearance, nutritional value and overall acceptability of cakes.